Housing Affordability in New Zealand: Evidence from Household Surveys - David Law; Lisa Meehan (New Zealand Government, The Treasury, 2013)
Housing affordability has been a topic of much interest in New Zealand over recent years with the median house price increasing by over 50% between 2004 and 2008. The aim of this paper is to inform debate by drawing out evidence from two surveys: the Household Economic Survey (HES); and the Survey of Family, Income and Employment (SoFIE). In particular, the paper examines how patterns of house prices, expenditures, and home ownership have changed over time and across groups. A model which may be suggestive of whether or not an individual or couple is likely to find home-ownership affordable is also developed. This model incorporates information relating to four important influences of affordability: income; net wealth; house prices; and the structure of mortgage contracts (including the interest rate and mortgage term).
Keywords: R21; R31; R32; 330; Housing Affordability; House Prices; Homeownership; Housing Expenditures; Rent; Mortgage Payments